Spatial and temporal variability in the δ18Ow and salinity compositions of Gulf of Maine coastal surface waters. (1st April 2017) - Whitney, Nina M.; Wanamaker, Alan D.; Kreutz, Karl J.; Introne, Douglas S.
Abstract: Hydrographic variability and dynamics in the Gulf of Maine are examined through the investigation of δ 18 O w and salinity properties of coastal surface waters. Data from Gulf of Maine waters sampled over a decade, from 2003 to 2015, including a suite of samples that were collected monthly from April 2014 to March 2015, are presented. These water samples fall on a mixing line between Maine River Water (MRW) and Scotian Shelf Water (SSW). However, slope waters likely also contribute to these surface waters. The seasonal variability in water samples collected during 2014 and 2015 indicates the strong influence of river runoff on coastal Gulf of Maine surface water properties. The coastal Gulf of Maine mixing line presented in this paper is a needed baseline for reconstructing hydrographic variability in bicarbonates using oxygen isotopes. Abstract : Highlights: Coastal waters fall on a 18 O-salinity mixing line between river water and Scotian Shelf Water. Monthly changes in surface water composition are largely influenced by river runoff. Ocean currents influence surface waters more in the summer and fall when river runoff is lower.